2023
DOI: 10.3390/ani13030360
|View full text |Cite
|
Sign up to set email alerts
|

Full-Fat Black Soldier Fly Larvae Meal in Diet for Tambaqui, Colossoma macropomum: Digestibility, Growth Performance and Economic Analysis of Feeds

Abstract: Black soldier fly (BSF, Hermetia illucens) larvae is a prominent ingredient in aquafeeds due to its high protein and energy contents. This study evaluated the digestibility of full-fat BSF larvae meal (FF-BSFL) and its inclusion in diets for tambaqui, Colossoma macropomum. The apparent digestibility coefficient of FF-BSFL for protein and energy was around of 88%, corresponding to 33.55% and 21.61 MJ kg−1 of digestible protein and energy, respectively. For the feeding trial, tambaqui juveniles (53.23 ± 1.07 g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The defatted BSFL meal (D-BSFL) is produced by partial or total fat extraction using pressing or organic solvents, and the resulting defatted meal is then posteriorly dried and ground. D-BSFL has around 60% protein and 10-12% lipid content (Barroso et al, 2014;Monteiro dos Santos et al, 2023). The full-fat BSFL (FF-BSFL) meal is easy to produce by drying and posteriorly grinding.…”
Section: Protein Meal Bsf Protein Meal Has High-quality Amino Acids L...mentioning
confidence: 99%
“…The defatted BSFL meal (D-BSFL) is produced by partial or total fat extraction using pressing or organic solvents, and the resulting defatted meal is then posteriorly dried and ground. D-BSFL has around 60% protein and 10-12% lipid content (Barroso et al, 2014;Monteiro dos Santos et al, 2023). The full-fat BSFL (FF-BSFL) meal is easy to produce by drying and posteriorly grinding.…”
Section: Protein Meal Bsf Protein Meal Has High-quality Amino Acids L...mentioning
confidence: 99%
“…Resulted in a higher benefit − cost ratio with better return on investment compared to CPS [56] Yellow mealworms Broilers 4-12% supplementation The incremental levels of insect meal resulted in increased costs of poultry diets with reduced gross margins [57] Black soldier fly larvae Layers 25 and 100% Resulted in a positive benefit − cost ratio and return on investment. Hence, the inclusion levels were most suitable and cost-effective [13] Full fat black soldier fly larvae Fish 10.50% inclusion The inclusion level had the highest index of economic profitability [14] Defatted black soldier fly larvae Fish Up to 100% replacement of fishmeal Increased economic efficiency [58] Black soldier fly larvae Fish 75% replacement of fishmeal Significantly reduced feed costs and resulted in higher economic returns [59] Black soldier fly larvae Pigs Up to 100% replacement of fishmeal Insect meal inclusion had the same benefit − cost ratio and return on investment compared to fishmeal as a CPS in pig diets [60] Black soldier fly larvae -5 to 50% replacement of fish meal and soybean meal Increased economic benefits [29] [12] companies or farms require expensive equipment such as oil extraction machines, incubators, proper storage, and special diets for successful rearing [17,37].…”
Section: Insect Type (Dry) Animal Type Insect Meal Inclusion Conclusi...mentioning
confidence: 99%
“…According to Fig. 1, black soldier fly larvae are currently the most expensive insects in $ per kg although they are currently the most preferred insects as feed for animals [14]. This may have a significant influence on the total costs of incorporating various insect meals in animal diets regardless of their nutritional and environmental benefits.…”
Section: Insect Type (Dry) Animal Type Insect Meal Inclusion Conclusi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research has shown that tambaqui can be fed with full-fat BSFL to a replacement level of 50% of the commercial feed [15], and the full-fat or defatted BSFL can be added up to 15.75% [16] or up to 30%, respectively, in extruded feed without compromising tambaqui growth performance [17]. These studies were carried out with BSFL as a commercial feed substitute or as an ingredient in regular fish feed formulations, using ingredients such as soybean, corn, and wheat middlings.…”
Section: Introductionmentioning
confidence: 99%